Preparation and characterization of sol-gel derived UV-curable organo-silica-titania hybrid coatings - KAYAMAN APOHAN, NİLHAN (ELSEVIER SCIENCE SA, 2007)
In this work, UV-curable organic-inorganic hybrid coatings based on cycloaliphatic epoxyacrylate were prepared by sol-gel technique. Acid catalyzed solutions of tetraethylorthosilane (TEOS) containing Ti:acac complex were used as an inorganic precursors. UV-curable, transparent hybrid coating materials were applied on plexiglass substrates and their coating performance was investigated by the analyses of various tests such as hardness, gloss, cross-cut adhesion tests, stress-strain test and optical transmission. The mechanical measurements showed that, the tensile properties of coatings underwent an abrupt change from a brittle to a tough material when the inorganic part was incorporated into the cycloaliphatic epoxy acrylate based organic network. UV-vis transmission spectroscopy results indicated that the hybrid materials with high titanium content have good transparences. The thermal behaviour of the coatings was also evaluated. It is observed that the thermal stability of the hybrids is enhanced with incorporation of sol-gel precursor. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: sol-gel; organic-inorganic hybrid; UV-curable; coating; SILANE